2018
DOI: 10.1093/cid/ciy514
|View full text |Cite
|
Sign up to set email alerts
|

The Candidate Blood-stage Malaria Vaccine P27A Induces a Robust Humoral Response in a Fast Track to the Field Phase 1 Trial in Exposed and Nonexposed Volunteers

Abstract: This trial was registered in clinicaltrials.gov (NCT01949909) and www.pactr.org (PACTR201310000683408).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…We previously reported that GLA-SE formulation induced higher anti-P27A titers than Alum, and that pre-exposed subjects exhibited lower humoral responses as compared to unexposed subjects. Furthermore, an increase in the dose of GLA-SE in the vaccine formulation was associated with an increase in antibody titers (5,15). We observed that the antibody responses directed to the 20-mer peptides had the same intensity profile as anti-P27A.…”
Section: Antibody Response and Fine-specificitymentioning
confidence: 70%
See 4 more Smart Citations
“…We previously reported that GLA-SE formulation induced higher anti-P27A titers than Alum, and that pre-exposed subjects exhibited lower humoral responses as compared to unexposed subjects. Furthermore, an increase in the dose of GLA-SE in the vaccine formulation was associated with an increase in antibody titers (5,15). We observed that the antibody responses directed to the 20-mer peptides had the same intensity profile as anti-P27A.…”
Section: Antibody Response and Fine-specificitymentioning
confidence: 70%
“…P27A formulated in Alum or in GLA-SE was studied in parallel in a phase 1a clinical trial in Lausanne, Switzerland (CH) and in a 1b clinical trial in Bagamoyo, Tanzania (TZ) (15). Trials were registered in clinicaltrials.gov (NCT01949909) and www.…”
Section: Human Samplesmentioning
confidence: 99%
See 3 more Smart Citations